Growth of private university business following “oligopoly” and “SME” approaches: an impact on the concept of university and on society - Alam, Gazi Mahabubul; Parvin, Morsheda; Roslan, Samsilah (Emerald, 2021)
Purpose: Universally, university is considered as the apex body which is ethically obliged to present a substantial society. In doing so, universities often innovate dynamic business models and theories. Ideally, the countries whose universities contribute for better and sustainable business growth are the advanced one. However, universities themselves should be the business organisation – an argument is yet to receive attention. Although literature lacks in the area of education business especially university provision, the sector behaves as business entity after the inception of private sector. Therefore, this paper aims to explore the paradigm transformation of university sector and its impact on the society. Design/methodology/approach: Given the differentiated nature of research questions, multiple techniques are used to collect the data. However, this research adopts the norms of qualitative methods. Both secondary and primary data are used. While secondary data are collected by University Grants Commission (UGC), primary data are collected through interviews. Findings: Findings show that the development of university sector started following monopoly model. More than half a century, the same model was continued. Thereafter, duopoly model was introduced which carried until the inception of private sector. The growth of private sector followed oligopoly model which was further extended to small and medium enterprises (SMEs). These days, society compares university with “diploma mill”, as production of knowledge and civic society is longer than the part of the core business of university. Consequently, compromising with research is to be judged as a threat to overall development that includes business and social development. Originality/value: A few studies have been published in the area of private university. To the best of the authors’ knowledge, none covers the oligopoly-ism and SME-ism behaviour of university and its impact on the concept of university and on the society. Therefore, this project aims to understand the norms of university business and its substantial contribution on the social change.